Effect of Biofertilizers and Chemical Fertilizers on Growth, Yield and Quality of Onion (Allium cepa L.) - Pal, Vikram; Maurya, Vasudha; Singh, Narayan; Kondal, Priya; Kaur, Ramandeep; Sharma, Sonika; Sharma, Ashutosh; Kumar, Rahul (International Journal of Economic Plants, 2025)
A field experiment conducted during the 2022–2023 rabi season (Nov-April) at DAV University, Jalandhar (Punjab) aimed to assess the impact of biofertilizers and chemical fertilizers on onion growth, yield, and quality. Variety PRO 7 was selected for the study. Eleven treatments viz., T1 (Control), T2 (NPK 100%), T3 (NPK 50%), T4 (Azotobacter 100%), T5 (Azospirillium100%), T6 (VAM 100%), T7 (NPK 50%+Azotobacter 50%), T8 (NPK 50% + Azospirillium 50%), T9 (NPK 50%+VAM 50%), T10 (NPK 50%+Azotobacter 50%+Azospirillium 50%), T11 (NPK 50%+Azotobacter 50%+Azospirillium 50%+VAM 50%) were arranged in a randomized block design with three replicatesThe result of experiment showed that T10 (NPK 50%+Azotobacter 50%+Azospirillium 50%) consistently exhibited superior performance, showcasing substantial improvements in crucial variables such as the number of leaves plant-1, number of rings bulb-1, plant height, chlorophyll a content, chlorophyll b content, and total chlorophyll content. While, T11 showed maximum bulb yield plot-1 and ha-1, as well as elevated levels of ascorbic acid and chlorophyll b. T9 displayed significant advancements in growth and quality parameters, including plant height, neck thickness, and total chlorophyll content and T6 showed maximum TSS (oBrix) content in onion. The economic analysis conducted as part of this study revealed that T11 yielded the highest gross income, net income, and benefit-cost ratio.